Multiseptate gallbladder presenting with biliary colic. Issue 9 (6th September 2022) - Hopmann, Peter; Tan, Ellen; Lo, David
Abstract: Common diagnoses associated with right upper quadrant and epigastric pain include cholecystitis, peptic ulcer disease (PUD), biliary colic, gastroesophageal reflux disease (GERD) and irritable bowel syndrome (IBS). Multiseptate gallbladder is a rare congenital anomaly that can cause symptoms of biliary colic, however it may present with atypical symptoms, which can prolong definitive diagnosis and treatment. We present a case of multiseptate gallbladder in a 21-year-old female who initially presented with GERD and IBS. After multiple failed treatment regimens for IBS, she ultimately was found to have multiseptate gallbladder and was successfully treated with cholecystectomy.